Clinical Features, Risk Factors, and Adhesive Tape Test Examination for Scabies at the Olak Kemang Community Health Center and Putri Ayu Community Health Center in Jambi City - Liza Oktaviani; Fitriyanti; Fairuz Quzwain; Rini Chrisna; Hafizah (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Scabies is a contagious skin disease that remains a public health problem, especially in areas with high population density and poor sanitation. This study aims to determine the demographic characteristics, clinical presentation, risk factors, and adhesive tape test results in scabies patients at the Olak Kemang Community Health Center and the Putri Ayu Community Health Center in Jambi City. The study used a descriptive observational design with a cross-sectional approach. The population was all scabies patients treated at both community health centers during the study period, while a sample of 43 respondents was determined using the Lemeshow formula with a purposive sampling technique. The research instruments included a questionnaire on demographic characteristics and risk factors, a clinical observation sheet, and an adhesive tape test. Data were analyzed using univariate analysis in the form of frequency distributions and percentages. The results showed that most patients were school-aged children, females, had no education up to elementary school or equivalent, and were unemployed. Lesions were most commonly found on the upper and lower extremities, with papules as the dominant lesion. Most respondents had poor personal hygiene, unhealthy basic sanitation, and low socioeconomic status, while positive adhesive tape test results were found in 7.0% of respondents. This study concluded that the characteristics of scabies patients at the study site were dominated by behavioral and environmental factors, while the adhesive tape test only identified a small proportion of cases, making it more appropriate to use as a supporting examination for clinical diagnosis.